Intravital imaging of hair-cell development and regeneration in the zebrafish - Lopez-Schier, Hernan; Pinto-Teixeira, Filipe; Muzzopappa, Mariana; Swoger, Jim; Mineo, Alessandro; Sharpe, James (Frontiers in Neuroanatomy, 2013)
Direct videomicroscopic visualization of organ formation and regeneration in toto is a powerful strategy to study cellular processes that often cannot be replicated in vitro. Intravital imaging aims at quantifying changes in tissue architecture or subcellular organization over time during organ development, regeneration or degeneration. A general feature of this approach is its reliance on the optical isolation of defined cell types in the whole animals by transgenic expression of fluorescent markers. Here we describe a simple and robust method to analyze sensory hair-cell development and regeneration in the zebrafish lateral line by high-resolution intravital imaging using laser-scanning confocal microscopy (LSCM) and selective plane illumination microscopy (SPIM). The main advantage of studying hair-cell regeneration in the lateral line is that it occurs throughout the life of the animal, which allows its study in the most natural context. We detail protocols to achieve continuous videomicroscopy for up to 68 hours, enabling direct observation of cellular behavior, which can provide a sensitive assay for the quantitative classification of cellular phenotypes and cell-lineage reconstruction. Modifications to this protocol should facilitate pharmacogenetic assays to identify or validate otoprotective or reparative drugs for future clinical strategies aimed at preserving aural function in humans.